2016
DOI: 10.1016/j.jgeb.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Algal production of nano-silver and gold: Their antimicrobial and cytotoxic activities: A review

Abstract: The spreading of infectious diseases and the increase in incidence of drug resistance among pathogens have made the search for new antimicrobials inevitable, similarly is the cancer disease. Nowadays, there is a growing need for biosynthesized nanoparticles (NPs) as they are one of the most promising and novel therapeutic agents of biological origin. The unique physicochemical properties of the nano silver (Ag-NPs) as well as nano gold (Au-NPs) when combined with the growth inhibitory capacity against microbes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
29
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(31 citation statements)
references
References 116 publications
1
29
0
1
Order By: Relevance
“…ere are four ways to synthesize microalgae nanoparticles: Several microalgal species have been exploited for the biosynthesis of nanomaterials by using their extracted biomolecules [29,30]. To obtain gold nanoplates, the microalgal biomass is first lyophilized and then it is subjected to RP-HPLC, i.e., reverse-phase high performance liquid chromatography, until the gold shape-directing protein (GSP), which is responsible for directing the shape of nanoparticles, is isolated.…”
Section: Microalgal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…ere are four ways to synthesize microalgae nanoparticles: Several microalgal species have been exploited for the biosynthesis of nanomaterials by using their extracted biomolecules [29,30]. To obtain gold nanoplates, the microalgal biomass is first lyophilized and then it is subjected to RP-HPLC, i.e., reverse-phase high performance liquid chromatography, until the gold shape-directing protein (GSP), which is responsible for directing the shape of nanoparticles, is isolated.…”
Section: Microalgal Nanoparticlesmentioning
confidence: 99%
“…Metallic nanoparticles can be synthesized by both live and died dried biomasses. Algae such as Chlorella vulgaris, Spirulina platensis, and Lyngbya majuscule have been reported for the efficient biosynthesis of silver nanoparticles [29].…”
Section: Microalgal Nanoparticlesmentioning
confidence: 99%
“…Recently, synthesis of silver nanoparticles using microorganisms, algae and plant extracts is already performed. The development of bionanotechnology in microalgae has shown that nano silver biosynthesis (nano silver) has increased the ability of microalgae as antimicrobial, antifungal and anticancer (Devi and Bimba, 2012;Rajesh et al, 2012;Sudha et al, 2013;Anuradha et al, 2014;Patel et al, 2015;Duong et al, 2016;El-Sheekh and El-Kassas, 2016;Rajeshkumar et al, 2012). Integration of microalgae with nano silver has wider the spectrum of antimicrobials capability in microalgae.…”
Section: Introductionmentioning
confidence: 99%
“…Eco-friendly nanoparticles have advantages especially in compatibility with pharmaceuticals over physical, chemical and microbial synthesis. High cost, inefficient treatment, contamination of toxic chemicals were leading to several effects when silver nanoparticles are being applied in the medical and pharmaceutical applications (Balashanmugam and Kalaichelvan, 2015;El-Sheekh and El-Kassas, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Microbicidal efficacy of phytosynthesized AgNPs using G. sylvestrae were represented in table 3. Among various metal nanoparticles, silver nanoparticles (AgNPs) in particular have been the focus of increasing interest due to their peculiar properties which can be tailored for a specific application by controlling the shape, size and morphology of the nanoparticles[48,49,50,51,52,53]. 400 µl of AgNPs remained resistant against Bacillus sp.…”
mentioning
confidence: 99%